The clinical utility of vestibular autorotation test in patients with vestibular migraine. - Thungavelu, Yogun; Wang, Wei; Lin, Peng; Chen, Taisheng; Xu, Kaixu (Acta Oto-Laryngologica, 2017)
Objective: To investigate the characteristics and clinical utility of vestibular autorotation test (VAT) in patients with vestibular migraine. Methods: This study included two groups, an experimental group (441 patients) and a control group (65 healthy subjects). Both groups undertook VAT; the parameters evaluated were horizontal gain/phase, vertical gain/phase and asymmetry. The differences in VAT results between the two groups were investigated. Results: There were no statistical differences between the VAT data of the control group when compared to the reference value from the manufacturer (p >.05). There were statistically significant differences in VAT results between the experimental and control group, namely elevated horizontal gain at frequency 2, 3, 4 and 5 Hz, horizontal phase delay at frequency 2, 4, 5 and 6 Hz, elevated vertical gain at frequency 2 6Hz and vertical phase delay at frequency 4 6Hz. Conclusion: The results of this study using VAT in VM patients demonstrate elevated horizontal gain, vertical gain and delay in horizontal phase, vertical phase. We suggest the application of VAT as a diagnostic tool which may provide objective evidence that can contribute to the diagnosis of VM and also in differential diagnosis.